Zinc-bromine flow battery diaphragm with bromine fixation effect, preparation method and application of zinc-bromine flow battery diaphragm

By setting a hydrophilic coating on the zinc-bromine flow battery separator and using micro-nanoparticle-sized inorganic particles, the problem of excessive pore size of the zinc-bromine flow battery separator is solved, which significantly reduces the risk of bromine element penetration and improves the battery's Coulomb efficiency and ion transmission capability are suitable for energy storage applications of zinc-bromide flow batteries.

CN119133498AInactive Publication Date: 2024-12-13INST OF WENZHOU ZHEJIANG UNIV +1

Patent Information

Application Number
CN202411620982.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The pore size of the existing zinc-bromine flow battery separator is too large, causing the penetration of the bromine element, causing the battery to self-discharge. The existing process is difficult to effectively reduce the pore size and improve the ionic conductivity.

Method used

A hydrophilic coating is provided on the porous membrane, and the porous membrane is activated by ozone treatment, plasma treatment or 60Coγ-radiation treatment, and the hydrophilic slurry is coated on it using ultrasonic coating technology. The hydrophilic slurry is hydrophilic. It consists of an adhesive, a stabilizer, a dispersant and a wetting agent to form a separator with a solid bromine effect.

Benefits of technology

Effectively adsorbs and fixes bromine element, reduces the self-discharge phenomenon of battery, improves Coulomb efficiency, reduces the risk of electrolyte leakage, and fills the channel structure with micro-nanoparticle-sized inorganic particles to reduce resistivity, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133498A_ABST
    Figure CN119133498A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc-bromine flow battery diaphragm with a bromine fixing effect, and a preparation method and application thereof, and relates to the field of zinc-bromine flow batteries. The zinc-bromine flow battery diaphragm comprises a porous diaphragm and a hydrophilic coating arranged on one side or two sides of the porous diaphragm, the hydrophilic coating is formed by coating an activated porous diaphragm with hydrophilic slurry, and the activation mode comprises any one of ozone treatment, plasma treatment or 60Co gamma-radiation treatment. According to the zinc-bromine flow battery diaphragm disclosed by the invention, the hydrophilic coating is arranged on the porous diaphragm, so that elemental bromine and polybrominated substances can be effectively adsorbed and fixed, the self-discharge phenomenon of a battery is reduced, and the coulombic efficiency of an electric pile is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of liquid flow batteries, and in particular to a zinc-bromine liquid flow battery diaphragm with a bromine-fixing function, a preparation method and an application thereof. Background Art

[0002] Since wind and solar power generation are easily affected by factors such as weather, they are discontinuous and unstable, which will cause impacts on the power grid during their grid connection process, affecting the continuity and stability of power supply. Energy storage technology can solve the above problems and ensure the stability of the power supply. Among them, flow batteries have the advantages of deep discharge, modular control, and no geographical restrictions, and have gradually become a highly valued energy storage technology in the field of energy storage. Among flow batteries, zinc-bromine flow batteries are new flow batteries with zinc as the negative electrode, bromine as the positive electrode, and an aqueous solution of zinc bromide and additives as the electrolyte. In addition, zinc-bromine flow batteries not only have the characteristics of high energy density and high open circuit voltage (zinc-bromine: all-vanadium = 1.85 V: 1.26 V), but also have low cost, and are theoretically more suitable for large-scale energy storage devices.

[0003] For zinc-bromine flow batteries, the self-discharge problem of the battery has always restricted its development. During the operation of the battery, the bromine element generated at the positive electrode is extremely corrosive and penetrating. It will penetrate the microporous membrane into the negative electrode area and undergo a redox reaction with the zinc element at the negative electrode, thereby causing the battery to self-discharge and reduce the coulombic efficiency and energy efficiency of the battery. Reasonable regulation of the pore size of the membrane is the key to preventing the penetration of bromine element. During the operation of the zinc-bromine flow battery, the diameter of the bromine molecules and their complex molecules generated at the positive electrode is 5-8 Å (Xianjin Li et al., Adv. Mater., 2020, 20050364). However, even the existing commercial microporous membranes made by the most mature manufacturing process have an average pore size of more than 30nm. For zinc-bromine flow batteries, the pore size of the membrane is still too large.

[0004] Therefore, on the basis of the existing porous membrane, further reducing the pore size of the microporous membrane is the focus of attention in the field of zinc-bromine flow battery membranes. For example, patent CN 112968190 B proposes a method for post-processing of flat plate hot pressing. After the PE porous membrane is heated to a certain temperature, the micropores inside the membrane are reduced by recompression, thereby blocking the penetration of bromine molecules and improving the coulombic efficiency of the battery. Although this method can reduce the pore size of the membrane to a certain extent, the process is difficult to control and can easily cause the effective pores of the membrane to collapse, the proportion of pores connected is reduced, and the internal resistance of the membrane is greatly increased. Therefore, for zinc-bromine flow battery membranes, how to reduce the average pore size of the membrane while enhancing its ionic conductivity has become an urgent problem to be solved. Summary of the invention

[0005] The purpose of the present application is to provide a zinc-bromine liquid flow battery diaphragm, reduce the average pore size of the diaphragm, and reduce the risk of penetration of bromine and polybrominated substances.

[0006] To achieve the above objectives, the technical solution adopted in the present application is: to provide a zinc-bromine liquid flow battery diaphragm with bromine fixing function, including a porous diaphragm and a hydrophilic coating arranged on one or both sides thereof, wherein the hydrophilic coating is formed by coating a hydrophilic slurry on the activated porous diaphragm, and the activation method includes any one of ozone treatment, plasma treatment or 60Coγ-radiation treatment.

[0007] Preferably, the hydrophilic slurry is composed of a hydrophilic binder, a stabilizer, a dispersant, a wetting agent and a solvent, wherein the hydrophilic binder is a hydrophilic linear polymer having a phthalazine structure or a phthalazinone structure in the main chain or in the side chain.

[0008] As another preference, the hydrophilic binder is any one of sulfonated phthalazine poly(arylether nitrile sulfone), sulfonated naphthyridine poly(arylether nitrile sulfone), sulfonated phthalazine poly(arylether sulfone ketone) and sulfonated naphthyridine poly(arylether sulfone ketone) or a combination of more thereof.

[0009] As another preferred embodiment, the stabilizer is hydrophilic micro-nano inorganic particles, and the particle size of the micro-nano inorganic particles is in the range of 0.05 to 1 µm.

[0010] As another preference, in the hydrophilic slurry, the sum of the masses of the hydrophilic binder, the stabilizer, the dispersant and the wetting agent accounts for 10% to 50% of the total mass.

[0011] As another preference, the dispersant is any one or more combinations of triethyl phosphate, sodium carboxymethyl cellulose, polyamic acid salt, polyacrylic acid, polyacrylic acid salt, polyacrylamide, polyethylene glycol, polyethylene oxide, polyvinyl alcohol, and polyvinyl pyrrolidone.

[0012] More preferably, the wetting agent is any one or more combinations of alkyl sulfonates, alkylbenzene sulfonates, allyl sulfonates, vinyl sulfonates, allyl phosphates, and sulfosuccinates.

[0013] The present application also provides a method for preparing a zinc-bromine liquid flow battery membrane with a bromine-fixing effect, comprising the following preparation steps: S1: dissolving a hydrophilic adhesive, a stabilizer, a dispersant and a wetting agent in a solvent to obtain a hydrophilic slurry with a solid content of 10% to 50%; S2: activating a porous membrane to obtain an activated porous membrane, wherein the activation method includes ozone treatment, plasma treatment or 60Coγ-radiation treatment; S3: applying the hydrophilic slurry to one side or both sides of the activated porous membrane by ultrasonic coating, and drying the hydrophilic slurry after solidification to obtain the zinc-bromine liquid flow battery membrane with a bromine-fixing effect.

[0014] As another preferred embodiment, in the step S3, the hydrophilic slurry is dried by freezing, and the freeze-drying temperature range is -50~5°C.

[0015] The present application provides a zinc-bromine liquid flow battery, comprising any of the above-mentioned zinc-bromine liquid flow battery diaphragms with bromine-fixing function, or the zinc-bromine liquid flow battery diaphragm with bromine-fixing function prepared by any of the above-mentioned preparation methods.

[0016] Compared with the prior art, the beneficial effects of this application are: (1) The zinc-bromine flow battery diaphragm of the present application has a hydrophilic coating on the porous diaphragm, which can effectively adsorb and fix bromine and polybrominated substances, reduce the self-discharge of the battery, and improve the coulombic efficiency of the battery stack; (2) The zinc-bromine flow battery diaphragm of the present application uses hydrophilic inorganic particles with micro-nano particle sizes, which are filled in the pore structure on the surface of the porous diaphragm, reducing the proportion of large pores and blind holes and reducing the risk of electrolyte leakage; (3) The hydrophilic slurry of the present application uses a hydrophilic adhesive, a stabilizer, a dispersant and a wetting agent. The substances can produce hydrogen bonds, which is helpful for the dispersion of the dispersant and has a good compatibility effect. The prepared hydrophilic slurry has stable performance and no obvious precipitation or stratification phenomenon occurs, which is conducive to the continuous and large-scale production of the zinc-bromine liquid flow battery diaphragm coating layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the pore size distribution diagram of the liquid flow battery membrane tested by the capillary method in Example 5.

[0018] Figure 2 This is the pore size distribution diagram of the flow battery membrane of comparative example 4 tested by capillary method.

[0019] Figure 3 This is the pore size distribution diagram of the liquid flow battery membrane of Example 5 tested by mercury intrusion testing.

[0020] Figure 4 This is the pore size distribution diagram of the flow battery diaphragm of comparative example 4 tested by mercury intrusion method.

[0021] Figure 5 This is the pore size distribution diagram of the liquid flow battery membrane tested by the gas-liquid method in Example 5.

[0022] Figure 6 This is the pore size distribution diagram of the liquid flow battery membrane of Comparative Example 4 tested by the gas-liquid method.

[0023] Figure 7 This is the pore size distribution diagram of the liquid-liquid method test of the liquid flow battery membrane in Example 5.

[0024] Figure 8 This is the pore size distribution diagram of the liquid-liquid method test of the liquid flow battery membrane of Comparative Example 4.

[0025] Fig. 9 This is the SEM electron microscope test image of the liquid flow battery membrane in Example 5.

[0026] Fig.10 This is the SEM electron microscope test image of the flow battery membrane of comparative example 4. DETAILED DESCRIPTION

[0027] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0028] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0029] The present application provides a zinc-bromine liquid flow battery diaphragm with a bromine-fixing function, comprising a porous diaphragm and a hydrophilic coating arranged on one or both sides thereof. The hydrophilic coating can reduce the penetration rate of bromine element and polybromine generated by the battery, and at the same time reduce the resistivity of the diaphragm, thereby improving the energy efficiency of the battery.

[0030] The hydrophilic coating is formed by coating the hydrophilic slurry on the activated porous membrane. The activation methods include ozone treatment, plasma treatment, 60 One or more combinations of Coγ-irradiation treatments. One or both sides of the porous membrane need to be activated with a hydrophilic coating.

[0031] The hydrophilic slurry is composed of a hydrophilic binder, a stabilizer, a dispersant, a wetting agent and a solvent, wherein the sum of the mass of the hydrophilic binder, the stabilizer, the dispersant and the wetting agent accounts for 10% to 50% of the total mass of the hydrophilic slurry. In terms of mass parts, the hydrophilic slurry is composed of 2 to 70 parts of a hydrophilic binder, 5 to 60 parts of a stabilizer, 1 to 10 parts of a dispersant, 0.1 to 5 parts of a wetting agent and the remaining solvent.

[0032] The hydrophilic adhesive is a hydrophilic linear polymer containing a phthalazinone structure or a phthalazinone structure in the main chain or side chain. Specifically, it can be any one or a combination of sulfonated phthalazinone polyarylether nitrile sulfone, sulfonated phthalazinone polyarylether nitrile sulfone, sulfonated phthalazinone polyarylether sulfone ketone and sulfonated phthalazinone polyarylether sulfone ketone. The phthalazinone structure or phthalazinone structure contained in the hydrophilic adhesive structure of the present application contains a heterocyclic ring containing a nitrogen atom, in which the electron cloud density in the heterocyclic ring is unevenly distributed, and the nitrogen atom presents a certain positive charge, which can adsorb and fix the negatively charged polybrominated substances generated in the zinc-bromine liquid flow battery.

[0033] The present application forms a hydrophilic coating by coating a hydrophilic slurry on an activated porous diaphragm, which has the following four beneficial effects: First, the hydrophilic coating contains a linear polymer with a nitrogen heterocyclic structure as a hydrophilic adhesive, which can effectively adsorb and fix free bromine and polybrominated substances in the electrolyte, thereby reducing the self-discharge of the battery and improving the battery CE.

[0034] Second, applying the hydrophilic coating can reduce the average pore size of the porous diaphragm. The reduced pore size inhibits the penetration of bromine molecules caused by self-discharge of the battery stack, further improving the coulombic efficiency of the battery stack.

[0035] Third, the hydrophilic coating has the function of modifying the pore walls inside the porous membrane. Since the hydrophilic slurry is rich in sulfonic acid groups and carboxyl groups, the modified membrane pore walls are negatively charged. Based on the principle of "like charges repel each other", the Br formed by the self-complexation of bromine molecules can be repelled. 3- Br 5- Particles such as these can further improve the Coulombic efficiency of the battery stack.

[0036] Fourth, in order to improve the ion transmission capacity of the diaphragm and compensate for the increased resistance due to the reduction in the pore size of the diaphragm, the hydrophilic slurry is rich in sulfonic acid groups and carboxyl groups with ion exchange capacity, which can increase the transmission rate of zinc ions. At the same time, the hydrophilicity of the diaphragm is enhanced, which can reduce the interface resistance between the aqueous electrolyte of the zinc-bromine flow battery and the diaphragm and increase the reaction rate of the active substance.

[0037] The stabilizer is a hydrophilic micro-nano-sized inorganic particle. In some preferred embodiments, the particle size of the inorganic particle ranges from 0.05 to 1 μm.

[0038] The stabilizer of the present application is hydrophilic inorganic particles with micro-nano particle size. While forming a hydrophilic coating, it can fill the macropores and blind holes on the surface of the porous diaphragm, reduce the proportion of macropores and blind holes in the porous diaphragm, thereby reducing the probability of bromine penetration and reducing the risk of electrolytic leakage.

[0039] In some embodiments, the stabilizer is hydrophilic silicon dioxide. More preferably, the silicon dioxide is prepared by a gas phase method or a precipitation method, and has a specific surface area of ​​200-380 m 3 / g.

[0040] The dispersant is water-soluble and can be any one or more of triethyl phosphate, sodium carboxymethyl cellulose, polyamic acid salt, polyacrylic acid, polyacrylic acid salt, polyacrylamide, polyethylene glycol, polyethylene oxide, polyvinyl alcohol, and polyvinyl pyrrolidone. In a more preferred embodiment, the HLB value of the dispersant is 8 to 15.

[0041] In some embodiments, the wetting agent can be any one or more of alkyl sulfonates, alkylbenzene sulfonates, allyl sulfonates, vinyl sulfonates, allyl phosphates, and sulfosuccinates.

[0042] In some embodiments, the porous separator can be any one of a polyethylene-based film, a polypropylene-based film, a polyimide-based film, a polyvinylidene fluoride-based film, a polyethersulfone-based film, and a polyacrylonitrile-based film.

[0043] In some embodiments, the solvent may be any one of deionized water, ethanol, methanol, isopropanol, or a combination of more than one thereof.

[0044] The hydrophilic slurry selected in the present application includes a hydrophilic binder, a stabilizer, a dispersant, and a wetting agent. Hydrogen bonds can be generated between the hydrophilic binder and the hydrophilic stabilizer, dispersant, and wetting agent, and the wetting agent can act as an auxiliary dispersant and has a good compatibility effect with the dispersant, so that the hydrophilic slurry prepared in the present application has stable performance and no obvious precipitation, stratification, etc., which is conducive to the continuous and large-scale production of the zinc-bromine liquid flow battery separator coating layer.

[0045] The present application also provides a method for preparing a zinc-bromine flow battery diaphragm, comprising the following preparation steps: S1: dissolving a hydrophilic binder, a stabilizer, a dispersant and a wetting agent in a solvent to obtain a hydrophilic slurry having a solid content of 10% to 50%; S2: activating the porous membrane to obtain an activated porous membrane; S3: The hydrophilic slurry is coated on one or both sides of the activated porous membrane by ultrasonic coating, and the hydrophilic slurry is dried after solidification to obtain a zinc-bromine liquid flow battery membrane with bromine fixing function of the present application.

[0046] In some embodiments, the activation method includes ozone treatment, plasma treatment or 60 Co γ-irradiation treatment.

[0047] In some preferred embodiments, the porous membrane is treated with plasma, and the activation atmosphere may be any one of air, nitrogen and helium.

[0048] This application breaks the traditional treatment method of porous diaphragms. It uses high-energy particles such as electrons, ions and free radicals in plasma to react with porous diaphragm materials to produce active groups such as hydroxyl and carboxyl groups, thereby reducing the surface energy of the porous diaphragm, thereby enhancing the adhesion of the hydrophilic coating on the surface and internal pores of the porous diaphragm, avoiding the risk of hydrophilic coating falling off due to repeated flushing of the strong acidic electrolyte of the zinc-bromine flow battery during the operation of the battery stack, and greatly extending the life of the battery stack with efficient operation.

[0049] Traditional coating techniques include dipping, which can only utilize the penetration force of the slurry itself. In essence, the slurry cannot enter the pores of the diaphragm and only floats on the surface of the diaphragm, causing the resistance of the porous diaphragm to decrease after coating. However, the ultrasonic coating technology is used in step S3 of the present application, which creatively utilizes the energy of ultrasonic waves to enhance the penetration force of the hydrophilic slurry, so that the hydrophilic slurry can penetrate into the pores inside the porous diaphragm, modify the pore structure, and reduce the pore size to prevent bromine penetration.

[0050] In some embodiments, the preparation method of the zinc-bromine flow battery diaphragm with bromine fixation function of the present application comprises the following preparation steps: S1: Add the hydrophilic adhesive to the solvent, stir and dissolve for 20-30 min, add the stabilizer, dispersant and wetting agent after the hydrophilic adhesive is completely dissolved, stir and dissolve for 15-25 min to form a hydrophilic slurry with a solid content of 10%-50% and a viscosity of 50-500 cp; S2: activating the porous membrane in a plasma processor chamber at a temperature of 20-50°C and a vacuum degree of 100-1000 Pa to obtain an activated porous membrane; S3: placing the hydrophilic slurry in an ultrasonic coating tank, coating the hydrophilic slurry on one or both sides of the activated porous membrane in ultrasound, and freeze-drying the hydrophilic slurry after solidification to obtain a zinc-bromine liquid flow battery membrane with bromine fixing function of the present application.

[0051] In some preferred embodiments, the porosity of the porous membrane base film is 30% to 70%, preferably 40% to 60%. The pore size of the porous membrane is 30 to 100 nm, preferably 30 to 50 nm. The thickness of the porous membrane is 0.3 to 1.1 mm; the resistivity ranges from 0.4 to 1.2 Ω·dm.

[0052] In some preferred embodiments, the ultrasonic time in step S3 is 30-300 s, and the ultrasonic frequency is 28-40 KHz.

[0053] In some preferred embodiments, the freeze-drying temperature ranges from -50 to 5°C, the drying time is 10 to 15 h, and the vacuum degree is 100 to 500 Pa.

[0054] Example 1 S1: Add 50 g of hydrophilic binder to 900 g of solvent, stir for 25 min, stir at 100 R, after the hydrophilic binder is completely dissolved, gradually add 40 g of stabilizer, 7 g of dispersant and 3 g of wetting agent, stir and disperse while adding, stir at 50 R, disperse at 600 R, stir for 15 min, and after stirring evenly, obtain a hydrophilic slurry with a solid content of 10%; S2: The polyethylene base film is placed in a plasma processor chamber at a temperature of 25 °C and a vacuum degree of 100 Pa for a treatment time of 100 s to obtain an activated porous membrane; wherein the polyethylene base film has a porosity of 65%; a pore size of 35 nm; a base film thickness of 0.65 mm; and a resistivity of 1.2 Ω·dm; S3: Pour the hydrophilic slurry into an ultrasonic coating tank and coat it on both sides of the activated porous membrane. The ultrasonic time is 30 seconds and the ultrasonic frequency is 40 kHz. After the hydrophilic slurry solidifies, it is sent to a freeze dryer for drying at a temperature of -30±5°C, a drying time of 10 hours, and a vacuum degree of 500 Pa. After drying, a zinc-bromine liquid flow battery membrane with bromine fixing effect of the present application is obtained.

[0055] Example 2 In step S2, the porous diaphragm polyethylene-based film is replaced with a polyvinylidene fluoride-based film, and in step S3, the ultrasonic time is adjusted to 300 s, and the freeze-drying is adjusted to use a forced air oven to dry at a temperature of 60°C for 10 h. The other preparation steps are consistent with the preparation steps in Example 1.

[0056] Example 3 The formula in S1 was adjusted to: 50 g of hydrophilic adhesive, 40 g of stabilizer, 7 g of dispersant and 3 g of wetting agent, and 300 g of solvent, to prepare a hydrophilic slurry with a solid content of 25%; the ultrasonic time in step S3 was adjusted to 80 s; the other preparation steps were consistent with the preparation steps in Example 1.

[0057] Example 4 In step S2, the porous diaphragm polyethylene-based film is replaced with polyacrylonitrile; the formula in S1 is adjusted to: 50 g of hydrophilic adhesive, 40 g of stabilizer, 7 g of dispersant and 3 g of wetting agent, and 100 g of solvent, to prepare a hydrophilic slurry with a solid content of 50%; the other preparation steps are consistent with the preparation steps in Example 1.

[0058] Example 5 In step S2, the porous diaphragm polyethylene-based film is replaced with polyetheretherketone; the formula in S1 is adjusted to: 70 g of hydrophilic adhesive, 20 g of stabilizer, 7 g of dispersant and 3 g of wetting agent, 300 g of solvent, and a hydrophilic slurry with a solid content of 25% is prepared; the other preparation steps are consistent with the preparation steps in Example 3.

[0059] Example 6 In step S2, the porous diaphragm polyethylene-based film is replaced with polyimide; the formula in S1 is adjusted to: 30 g of hydrophilic adhesive, 60 g of stabilizer, 7 g of dispersant and 3 g of wetting agent, 300 g of solvent, and a hydrophilic slurry with a solid content of 25% is prepared; the other preparation steps are consistent with the preparation steps in Example 3.

[0060] Comparative Example 1 In step S3, ordinary coating method is adopted instead of ultrasonic coating, and other preparation steps are consistent with the preparation steps in Example 3.

[0061] Comparative Example 2 The S2 activation step is removed, and the hydrophilic slurry is directly coated on both sides of the porous membrane. The other preparation steps are consistent with the preparation steps in Example 3.

[0062] Comparative Example 3 The porous base membrane is only plasma activated without forming a hydrophilic coating, and the other preparation steps are consistent with the preparation steps in Example 3.

[0063] Comparative Example 4 The polyethylene film without any treatment was used as the separator of zinc-bromine flow battery.

[0064] Performance Testing 1. The porous membranes prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to pore size test, porosity test, resistivity test and static water contact angle test, respectively. In order to present the test results more clearly, the membrane coating formulas and performance test results of the embodiments and comparative examples were accurately recorded in Tables 1 and 2.

[0065] 2. Example 5 and Comparative Example 4 were subjected to capillary method, mercury injection method, gas-liquid method and liquid-liquid method pore size tests respectively. In the liquid-liquid method test of the diaphragm, the infiltrated liquid was isobutanol, and the displacement liquid was a saturated solution of isobutanol and deionized water; the diaphragm was cut into samples with a diameter of 40 mm using a cutter, placed in the test cavity, and the cavity was gradually pressurized, and the pressure P and the flow rate L of the displacement liquid were accurately recorded, where the pressure corresponding to the intersection of the semi-dry line and the wet line was the pressure of the average pore size, and then the pressure data was converted into pore size data according to the capillary conversion formula to obtain the average pore size. The results of the pore size test are recorded in Table 3.

[0066] Table 1 Performance test results of various embodiments

[0067] Analyzing the performance test results of Examples 1 to 4, the formula of the hydrophilic slurry solid phase is the same. As the concentration of the slurry is gradually increased, the pore size, porosity and static water contact angle of the diaphragm gradually decrease. In Example 4, it is speculated that due to the excessive solid content of the hydrophilic slurry, the slurry blocks most of the pore structure, the diaphragm porosity is greatly reduced, and then the diaphragm porosity is greatly increased. In Example 2, it is speculated that because the diaphragm is dried in an oven, the larger surface tension of the solvent during the volatilization process causes the pore structure of the diaphragm to collapse, causing the resistivity of the diaphragm to increase by 104% compared to the freeze-drying technology in Example 1, which is not conducive to the application of the diaphragm in batteries.

[0068] In Examples 3, 5 and 6, the solid content of the hydrophilic slurry is 25%. The material ratio of the solid phase is adjusted. The test results show that the pore size and static water contact angle will be further reduced by increasing the proportion of the hydrophilic binder, while the porosity and resistivity remain unchanged. In Example 6, the proportion of the stabilizer is increased, and the opposite conclusion is obtained. The pore size becomes larger and the porosity becomes smaller, and the resistivity and static water contact angle remain unchanged. It is speculated that because too much inorganic nano-ion stabilizer is filled in the blind holes of the diaphragm, the porosity is significantly reduced, but it does not affect the through holes of the diaphragm. The reduction of the hydrophilic binder will lead to a decrease in the thickness of the coating adsorbed inside the pore structure, so the diaphragm pore size becomes larger, and the resistivity caused by the decrease in porosity is compensated, so the resistivity of the diaphragm does not change.

[0069] Table 2 Performance test results of Example 3 and Comparative Examples 1 to 4

[0070] The performance test results of Example 3, Comparative Example 1 and Comparative Example 2 were analyzed. In Comparative Example 1, the pore size of the liquid flow battery diaphragm obtained by not using ultrasonic coating increased while the porosity decreased, and the resistivity increased by 36%. The performance test results showed that in the conventional coating form, the hydrophilic adhesive and stabilizer can only be filled in the blind holes on the surface of the diaphragm, but cannot penetrate into the porous diaphragm pore structure, resulting in a larger diaphragm pore size and a hydrophobic internal structure. The hydrophobic performance is greatly affected and manifested as an increase in the resistivity of the liquid flow battery diaphragm. The liquid flow battery diaphragm obtained in Comparative Example 2 has almost no change in pore size and porosity, and an increase in resistivity and static water contact angle. The test results show that activation can further improve the performance of the liquid flow battery diaphragm.

[0071] Comparative Examples 3 and 4 are two blank control experiments. Conventional polyethylene membranes are used as flow battery separators, and their pore size, porosity, resistivity and static water contact angle are all large, which are not suitable for flow battery separators and cannot improve the problem of bromine penetration. However, the pore size and porosity of the polyethylene membrane treated with plasma are almost the same as those of the untreated polyethylene membrane, and the resistivity and static water contact angle are slightly reduced. However, when used as zinc-bromine flow battery separators, the problem of bromine penetration cannot be solved.

[0072] As a comparative supplement, the zinc-bromine liquid flow battery membrane of Example 5 and the zinc-bromine liquid flow battery membrane of Comparative Example 4 were subjected to pore size tests using the capillary method, mercury injection method, gas-liquid method and liquid-liquid method, and the test results are recorded in Table 3 below. Figure 1 and Figure 2 The capillary method test pore size distribution diagrams of Example 5 and Comparative Example 4 are respectively, Figure 3 and Figure 4 The pore size distribution diagrams of the mercury intrusion method test of Example 5 and Comparative Example 4 are respectively, Figure 5 and Figure 6 The pore size distribution diagrams of the gas-liquid method test of Example 5 and Comparative Example 4 are respectively, Figure 7 and Figure 8 The pore size distribution diagrams of the liquid-liquid method test of Example 5 and Comparative Example 4 are shown respectively.

[0073] Table 3 Aperture test results of Example 5 and Comparative Example 4

[0074] The pore size test results show that in the test results of various pore size tests, the average pore size of the zinc-bromine flow battery membrane of Example 5 is smaller than that of the original polyethylene membrane, and the proportion of blind holes is significantly reduced, which shows that the technical solution of the present application effectively fills the hydrophilic slurry on the surface and in the pores of the porous membrane, effectively reducing the average pore size of the zinc-bromine flow battery membrane. The zinc-bromine flow battery membranes of Example 5 and Comparative Example 4 were tested by SEM electron microscopy. The test results of Example 5 are as follows: Fig. 9As shown, the SEM electron microscope test results of Comparative Example 4 are as follows Fig.10 As shown, the inorganic nanoparticle stabilizer is filled in the macropores of the porous diaphragm, reducing the proportion of blind holes and effectively reducing the risk of electrolyte leakage and penetration.

[0075] The zinc-bromine liquid flow battery diaphragm with bromine fixing function of the present application can significantly reduce the average pore size and blind hole ratio of the diaphragm, effectively reduce the risk of bromine penetration, and can obtain better resistivity and static water contact angle, and is suitable for application in zinc-bromine liquid flow battery systems.

[0076] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A zinc-bromine flow battery membrane with bromine-fixing function, characterized in that: The invention comprises a porous membrane and a hydrophilic coating disposed on one or both sides thereof, wherein the hydrophilic coating is formed by coating a hydrophilic slurry on the activated porous membrane, wherein the activation method comprises ozone treatment, plasma treatment or 60 Any of the Co γ-irradiation treatments.

2. The zinc-bromine liquid flow battery diaphragm with bromine fixation function according to claim 1, characterized in that: The hydrophilic slurry is composed of a hydrophilic adhesive, a stabilizer, a dispersant, a wetting agent and a solvent. The hydrophilic adhesive is a hydrophilic linear polymer having a phthalazine structure or a phthalazinone structure in the main chain or the side chain.

3. The zinc-bromine liquid flow battery diaphragm with bromine fixation function as claimed in claim 2, characterized in that: The hydrophilic binder is any one of sulfonated phthalazine poly(arylether nitrile sulfone), sulfonated naphthyridine poly(arylether nitrile sulfone), sulfonated phthalazine poly(arylether sulfone ketone) and sulfonated naphthyridine poly(arylether sulfone ketone) or a combination of more than one thereof.

4. The zinc-bromine liquid flow battery diaphragm with bromine fixation function as claimed in claim 2, characterized in that: The stabilizer is hydrophilic micro-nano inorganic particles, and the particle size of the micro-nano inorganic particles ranges from 0.05 to 1 μm.

5. The zinc-bromine liquid flow battery diaphragm with bromine fixation function as claimed in claim 2, characterized in that: In the hydrophilic slurry, the sum of the masses of the hydrophilic binder, the stabilizer, the dispersant and the wetting agent accounts for 10% to 50% of the total mass.

6. The zinc-bromine liquid flow battery diaphragm with bromine fixation function as claimed in claim 2, characterized in that: The dispersant is any one or more combinations of triethyl phosphate, sodium carboxymethyl cellulose, polyamic acid salt, polyacrylic acid, polyacrylic acid salt, polyacrylamide, polyethylene glycol, polyethylene oxide, polyvinyl alcohol, and polyvinyl pyrrolidone.

7. The zinc-bromine liquid flow battery diaphragm with bromine fixation function as claimed in claim 2, characterized in that: The wetting agent is any one or more combinations of alkyl sulfonates, alkylbenzene sulfonates, allyl sulfonates, vinyl sulfonates, allyl phosphates, and sulfosuccinates.

8. A method for preparing a zinc-bromine flow battery diaphragm having a bromine-fixing function, characterized in that: The method comprises the following preparation steps: S1: dissolving a hydrophilic binder, a stabilizer, a dispersant and a wetting agent in a solvent to obtain a hydrophilic slurry having a solid content of 10% to 50%; S2: activating the porous membrane to obtain an activated porous membrane, wherein the activation method includes ozone treatment, plasma treatment or 60 Coγ-irradiation treatment; S3: applying the hydrophilic slurry to one or both sides of the activated porous membrane by ultrasonic coating, and drying the hydrophilic slurry after solidification to obtain the zinc-bromine liquid flow battery membrane with bromine fixing function.

9. The method for preparing a zinc-bromine flow battery diaphragm having a bromine-fixing function according to claim 8, characterized in that: In the step S3, the hydrophilic slurry is dried by freezing, and the freeze-drying temperature range is -50~5°C.

10. A zinc-bromine flow battery, characterized in that: It comprises the zinc-bromine liquid flow battery diaphragm with bromine fixing function as described in any one of claims 1 to 7, or the zinc-bromine liquid flow battery diaphragm with bromine fixing function prepared by the preparation method as described in any one of claims 8 or 9.

Citation Information

Patent Citations

  • Composite film for flow energy storage battery and application thereof

    CN102867930A

  • Composite ultrafiltration or nanofiltration membrane for hydrogen-chlorine fuel cells, and preparation and application thereof

    CN103515629A

  • Preparation method of low-temperature sodium-sulfur battery diaphragm and low-temperature sodium-sulfur battery

    CN110247008A

  • Ceramic slurry, lithium ion battery diaphragm and lithium ion battery

    CN115642367A

  • Core-shell fluorine-containing acrylate copolymer emulsion as well as preparation method and application thereof

    CN115677937A

Cited By

  • Porous titania-carbon-composites, methods of making the same, and zinc-bromine flow batteries

    CN122822774A